CT-guided fine-needle localization of ground-glass nodules in re-aerated lung specimens: localization of solitary small nodules or multiple nodules within the same lobe - Li, Ming (Diagn Interv Radiol, 2015)
PURPOSE: We aimed to explore the value of localizing small ground-glass nodules (GGNs; <10 mm) or multiple GGNs within the same lobe in re-aerated lung specimens using CT-guided fine-needle localization. METHODS: Thirty-five lung specimens containing single small GGNs (<10 mm) and eight specimens containing two or more GGNs in the same lobe were re-aerated with an inflatable aerator. All lesions were localized via CT-guided fine-needle localization following re-aeration. The specimens were then sent for pathologic sampling and qualitative diagnosis. RESULTS: All 69 nodules from 43 cases were successfully localized using CT-guided fine-needle localization following re-aeration. CONCLUSIONS: CT-guided fine-needle localization of lesions in surgical specimens under constant, moderate mechanical aeration allows for the rapid and accurate localization of lesions and helps avoid damage from preoperative localization.